Integrasi Metode AHP-SAW untuk Evaluasi Kinerja Mitra Bisnis pada Sistem Manajemen Kemitraan Berbasis Web - Surya Darma Nasution; Nurhayati Nurhayati; Sri Wanti Nasution (Explorer, 2026)
Business partnership management in SMEs and companies is still largely conducted manually, making objective partner performance evaluation difficult. This study aims to integrate the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods to evaluate partner performance in a web-based partnership management system. AHP is used as the criteria weighting method through pairwise comparison validated by the Consistency Ratio (CR), while SAW is used for partner ranking. Four evaluation criteria were established: number of collaboration activities, active partnership duration, completeness of collaboration evidence, and number of expired MoUs without renewal. The AHP calculation produced criteria weights with a CR value of 0.0038 (< 0.1), indicating consistent judgment. Testing on five partners produced consistent rankings, with Partner C as the best-performing partner (preference value 1.0000). A comparative analysis between AHP-SAW and pure SAW (manual weighting) showed identical rankings (Spearman correlation = 1.000), yet AHP-SAW provided more objective and validated weighting justification. The developed system proved capable of producing objective, transparent, and measurable partner performance evaluations.